Komposisi Jenis dan Kelimpahan Makrozoobentos Epifauna Berdasarkan Jenis Mangrove yang Berbeda di Kecamatan Suppa, Kabupaten Pinrang: Composition Type and Abundance of Macrozoobenthos Epifauna Based on Different Mangrove species in Suppa District, Pinrang Regency - Muh Mansyawi; Joeharnani Tresnati; Moh Tauhid Umar (Jurnal Pengelolaan Perairan, 2022)
Mangroves have an important function in the food chain, which can support the life of various types of aquatic biota. One of the communities whose life cycle is relatively settled in the mangrove ecosystem is the macrozoobenthos. This study aims to analyze the relationship between mangrove species and the macrozoobenthos epifauna community including species composition, frequency of occurrence, density and Margalef index (species richness) in Suppa District, Kab. Pinrang. The research was conducted in April 2020 - June 2020 in Suppa District, Pinrang Regency, data identification was carried out at the Water Quality Laboratory of the Faculty of Marine and Fisheries Sciences, Hasanuddin University Makassar. The research stages include determining the location and research station, taking macrozoobenthos samples, measuring water quality, and analyzing data. The data collected included species composition, macrozoobenthos abundance, diversity index, uniformity index, dominance index, and nMDS. (non Multidimensional Scaling). The number of macrozoobenthos epifauna species found based on observations at the station with Avicennia sp. mangrove species andmangrove species Rhizopora sp. There are 5 species from 3 classes, namely Gastropods, Bivalves, and Malacostraca.. The abundance of macrozoobenthos epifauna in Rhizopora sp. higher than that of macrozoobenthos epifauna at stations with Avicennia sp. mangroves were Avicennia sp.dominated by gastropod macrozoobenthos epifauna,species, Cerithidea cingulatawhile macrozoobenthos epifauna at the station was Rhizopora sp. has a high level of uniformity and diversity which is indicated by the even number of individuals in each type of macrozoobenthos epifauna found.